Cold physical plasma selects for specific T helper cell subsets with distinct cells surface markers in a caspase‐dependent and NF‐κB‐independent manner. Issue 12 (7th November 2016) - Bekeschus, Sander; Rödder, Katrin; Schmidt, Anke; Stope, Matthias B.; von Woedtke, Thomas; Miller, Vandana; Fridman, Alexander; Weltmann, Klaus‐Dieter; Masur, Kai; Metelmann, Hans‐Robert; Wende, Kristian; Hasse, Sybille
Abstract : Exposure to cold physical plasma has been proposed to be of therapeutical value in oncology via the generation of a number of biologically relevant redox‐active molecules. Cancer cells can be recognized and eliminated by cells of the immune system, and accordingly many tumors are populated with these cells, among them T helper cells (TH cells). These lymphocyte population is crucial for effector immune responses against tumor antigens, in response to immunogenic cell death in malignant cells. However, a number of TH populations exists, each having distinct phenotypical features. Using a cold atmospheric pressure argon plasma jet, its redox activity was tested in different TH cell subpopulations to better understand the immunological consequences of potential antitumor plasma treatments in vivo. Abstract : T helper cells are an important leukocyte subset endogenously helping to fight human cancers, and treatment with a cold atmospheric pressure argon plasma jet is significantly less toxic in naïve lymphocytes with a phenotype preferential for tissue entry compared to central memory T cells. These naïve cells are capable of generating local immune responses to new antigens, granting plasma a possible role in directing immune responses in vivo.